The Role of the Regional People's Representative Council (DPRD) in Supervision of Regional Finance - Dimas Azhari; Sri Sudiarti (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
Budgeting is planning arranged systematically in form of numeral and stated in unit of monetary which covering entire company activities for particular period in the future. In arrangement of budget for public sector should be determined the allocation of amount of fund in each program and government activity in monetary unit. In this case, role of DPRD to monitor local finance is very needed, so that the program which has arranged can run effectively, efficient and economical. In addition, monitoring conducted by DPRD should be direct and indirectly. As for the direct monitoring was observing, investigating, and inspection, while the indirect monitoring was to learn the report accepted from implementation. Be sides, in implementation of monitoring the DPRD has special committee referred to Budgeting Committee.